2017
DOI: 10.1111/nmo.13239
|View full text |Cite
|
Sign up to set email alerts
|

An ANMSNASPGHAN consensus document on esophageal and antroduodenal manometry in children

Abstract: This review highlights some of the recent advances in pediatric esophageal and antroduodenal motility testing including indications, preparation, performance, and interpretation of the tests. This update is the second part of a two part series on manometry studies in children (first part was on anorectal and colonic manometry [Neurogastroenterol Motil. 2016;29:e12944]), and has been endorsed by the North American Society for Pediatric Gastroenterology, Hepatology and Nutrition (NASPGHAN) and the American Neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(112 citation statements)
references
References 90 publications
0
97
0
Order By: Relevance
“…Our center also does not routinely perform esophageal motility studies, but altered esophageal or pharyngeal motility is found in other disorders such as TEF/EA and cricopharyngeal achalasia in the aerodigestive population. 32 Therapies for such esophageal abnormalities, however, are sparse. 33,34 Despite these limitations, the GI aerodigestive evaluation objectively defined gastrointestinal tract anomalies, evaluated symptom correlation, and found histologic abnormalities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our center also does not routinely perform esophageal motility studies, but altered esophageal or pharyngeal motility is found in other disorders such as TEF/EA and cricopharyngeal achalasia in the aerodigestive population. 32 Therapies for such esophageal abnormalities, however, are sparse. 33,34 Despite these limitations, the GI aerodigestive evaluation objectively defined gastrointestinal tract anomalies, evaluated symptom correlation, and found histologic abnormalities.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, this study primarily looked at the reflux evaluation and not the other components of aerodigestive care. Our center also does not routinely perform esophageal motility studies, but altered esophageal or pharyngeal motility is found in other disorders such as TEF/EA and cricopharyngeal achalasia in the aerodigestive population . Therapies for such esophageal abnormalities, however, are sparse …”
Section: Discussionmentioning
confidence: 99%
“…The ADM study was performed as per previously described protocol . In brief, the study performance was divided into 4 phases: fasting (3‐hour); meal challenge (30‐minute) with postprandial recording (1‐hour); erythromycin (EES) challenge (infusion over 30‐minute and postinfusion recording of 1‐hour); and octreotide (OCT) challenge (1‐hour).…”
Section: Methodsmentioning
confidence: 99%
“…The ADM study was performed as per previously described protocol. 3 In brief, the study performance was divided into 4 phases: The ADM study was performed on two separate days. On day 1, recording began once the patient was fully awake and recovered from anesthesia.…”
Section: Antroduodenal Manometrymentioning
confidence: 99%
“…Esophageal dysmotility is a rare but troublesome problem in children; however, a prompt diagnosis may lead to adequate timely management. 1 Ineffective esophageal motility disorder (IEM) is one of the esophageal hypomotility disorder, and is associated with dysphagia, chronic vomiting, odynophagia, chest pain, or heartburn sensation. 1 Esophageal high-resolution manometry (HRM) with automated calculated parameters, including distal contractile integral (DCI), distal latency (DL), and 4-s integrated relaxation pressure (IRP-4s) to quantify the intraluminal pressure changes of the esophagus, were developed to assist in the diagnosis of esophageal hypomotility and spastic motor disorders in both adults and children.…”
Section: Introductionmentioning
confidence: 99%